ANALISIS TINGKAT LITERASI KEAMANAN SIBER SISWA DI SMP MUHAMMADIYAH 3 SAMARINDA BERDASARKAN PENGGUNAAN MEDIA SOSIAL - Rizqullah; Romisa, Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the level of cybersecurity literacy among students at SMP Muhammadiyah 3 Samarinda based on social media usage, identify related factors, and provide recommendations for improvement. This research employed a quantitative descriptive approach using a survey method. Data were collected through questionnaires distributed to 111 students and analyzed using descriptive statistics, including percentages, mean scores, and standard deviations with SPSS. The results indicate that students' cybersecurity literacy is categorized as very high, with an overall percentage of 83.34%. The highest percentage was found in the cyber threat awareness indicator (87.8%), while the lowest was in actions in responding to cyber threats (78.8%). Mean analysis showed that cyber threat awareness obtained the highest average score (3.51), whereas actions in responding to cyber threats obtained the lowest average score (3.14). The findings suggest that students generally possess good knowledge and awareness. Based on these findings, schools are encouraged to strengthen cybersecurity literacy through digital security education, seminars, workshops, and active involvement of teachers and parents in guiding students' digital activities.